The Correlation between Naturalistic Intelligence and Environmental Concern of Students of UIN Sulthan Thaha Saifuddin Jambi - Syifa Nurrahman; Salahuddin Salahuddin; Maimunah Permata Hati Hasibuan (Bioedukasi: Jurnal Pendidikan Biologi, 2025)
Environmental destruction in Indonesia is increasingly alarming since the country ranks as the fifth biggest waste producer globally. As the agents of change, students have a significant and strategic role in environmental conservation; however, observations at UIN Sulthan Thaha Saifuddin Jambi indicate that environmental awareness among students remains low. The focus of this research is to understand the correlation between natural intelligence and environmental concern of students in UIN Sulthan Thaha Saifuddin Jambi, which is examined using a quantitative approach with a correlational method to determine the link between the two variables. This research involved 99 students as respondents and was selected randomly using a simple random sampling technique; the data of this research were collected through questionnaires and interviews to measure the students’ natural intelligence and environmental concern. The results showed that most students have natural intelligence (64,6%) and environmental concern (72,7%) in the medium category. Correlation analysis Product Moment Pearson generates significant numbers 0,00<0,05 and calculated r 0,604>0,195, indicating a considerable correlation between the two variables in a strong category. Regression analysis resulted in the equation Y = 25,319 + 1,117X, with a practical contribution of 6, 4% of natural intelligence to the environmental concern, while other factors influenced the other 63,6%. The result reiterates the necessity of a comprehensive approach to increasing the environmental concern of the students, not only from natural intelligence development but also from other influential factors such as environmental knowledge, religious values, and access to environmental information